(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2020)
In this essay, the author posits the need for education to take a leading role in the wake of the 2020 COVID-19 pandemic. It is noted, in particular, how the disruptions to education caused by the pandemic exposed the fragility of education while also exacerbating inequalities as instruction went online. Because international education relies upon physical mobility the pandemic not only disrupted the education of millions of far-flung students but put their health, safety, and security at risk as borders closed and transportation was halted or became severely limited. The concept of “border-free” education is offered here as a way to minimize risks to internationally-mobile students (and scholars), while also removing barriers and expanding knowledge, diversity, and opportunities, particularly for the marginalized and vulnerable.